Robust Resource Allocation for Bidirectional Decode-and-Forward OFDM Relaying Systems with Network Coding and Imperfect CSI - Xiaolin Ma; Fangmin Li; Ilow, Jacek; Zhizhang Chen (IEEE VTS Vehicular Technology Conference (1999), 2014)
In this paper, we investigate the joint optimization of power allocation and subcarrier assignment in the OFDM bidirectional systems where two users exchange data assisted by multiple decode-and-forward (DF) relays. We assume the availability of imperfect channel state information (CSI) that contains a probabilistic uncertainty component and consider its worst effect when performing resource allocation. Moreover, we adopt dynamic network coding to exploit channel diversity. The objective of the resource allocation problem is to maximize the weighted sum rates of the two users subject to quality-of-service (QoS) requirements and individual power constraints. We formulate the problem as a mixed integer programming problem and solve it efficiently in an asymptotic manner by using the dual method. Simulation results show that the proposed scheme is robust to imperfect CSI and provides better performance compared to the scheme with static network coding.